Assessing the effectiveness of newborn resuscitation training and skill retention program on neonatal outcomes in Madhesh Province, Nepal. - Mala Chalise; Ranjan Dhungana; Michael K Visick; Robert B Clark (Public Library of Science (PLoS), 2022)
Intrapartum events leading to asphyxia at birth are among the leading causes of neonatal morbidity and mortality in Nepal. In response to this, the Nepal Ministry of Health and Population adopted Helping Babies Breathe (HBB) as a tool to improve neonatal resuscitation competencies. The effectiveness of HBB trainings has been well established. However, challenges remain in maintaining skills over time. Safa Sunaulo Nepal (SSN), with support from Latter-day Saint Charities (LDS Charities) designed an initiative for scaling up newborn resuscitation training and skills maintenance over time. This paper reports on the implementation of the SSN model of newborn resuscitation trainings and skill retention, and the changes in perinatal outcomes that occurred after the program. The program built capacity among facility-based trainers for the scale up and maintenance of resuscitation skills in 20 facilities in Madhesh Province, Nepal. A single external Mentor coached and assisted the facility-based trainers, provided general support, and monitored progress. Prospective outcome monitoring tracked changes in health metrics for a period of 14 months. Data was gathered on the neonatal health outcomes of 68,435 vaginal deliveries and 9,253 cesarean sections. Results indicate decreases in neonatal deaths under 24 hours of life (p<0.001), intrapartum stillbirths (p<0.001), and the number of sick newborns transferred from the maternity unit (p<0.001). During the program, facility-based trainers taught resuscitation skills to 231 medical personnel and supported ongoing skill retention. The SSN model for newborn resuscitation training and skills retention is a low-cost, evidence-based program focusing on facility-based trainers who are mentored and supported to scale-up and sustain resuscitation skills over time. Findings from the report are suggestive that the model had a substantial influence on critical neonatal outcomes. Future programs focused on improving neonatal outcomes may benefit by incorporating program elements of SSN model.